Steering Committee - Zantides, Evripides (My University, 2026)
https://aliveposterfestival.com/aboutWe are delighted to announce the list of artists selected for the exhibitions at Alive Poster Festival 2025. The competition received submissions from all over the world—a total of 565 posters from 44 countries